Morphological characterisation of camels in Katsina state, Nigeria, using path analysis - EMMANUEL ABAYOMI ROTIMI (Indian Journal of Animal Sciences)
This study assessed relationships between body weight and biometric traits and also the direct and indirect contributions of some biometric traits on body weight in camels. Data was obtained from 51 (27 female and 24 male) camels, including: heart girth (HGT), abdominal girth (ABG), rump height (RPH), shoulder height (SHT), ear length (EAL), fore leg length (FLL), hind leg length (HLL), neck length (NLT) and head length (HDL). Data was subjected to statistical analysis using IBM SPSS version 27.0.0. Female phenotypic correlations indicated that body weight had positive correlations with all the traits, with the highest correlation obtained with HGT and least with FLL. In male camels, correlations between body weight and biometric traits were all positive. The highest correlation was obtained with ABG and the weak with RPH. Path analysis on females showed that SHT had greatest direct effects on body weight and the greatest indirect effects was from HGT via ABG. However, HGT had the greatest direct effect on body weight in male camels and the highest indirect effects were similar to the female camels, observed in HGT via ABG. Information obtained from present research may assist farmers in the rural areas, who may not have access to weighing scales, to predict body weight of animals for management and marketing purposes. The outcome of the study may be useful management decision making and genetic improvement for breeders in selection for body weight improvement in camels.